Полікритеріальний метод оптимізації процесу освітлення при вирощуванні рослин в теплицях - Червінський, Л.С.; Сторожук, Л. О. (Енергетика і автоматика, 2017)
UDC 631:563POLYCRITERIAL METHOD OF OPTIMIZATION OF THE LIGHTING PROCESS IN GROWING OF PLANTS IN HEATINGSL. Chervinsky, L. Storozhuk                        Introduction. A characteristic feature of agricultural production at the present stage is that the share of electricity for lighting and radiation in the cost price of products has not only increased, but has become a determining factor. This leads to a change in approaches in the creation of technological processes and the construction of installations for optical technologies, which are based on increasing the energy efficiency of irradiating devices. For the solution of this problem the modeling of technological processes is widely used.Analysis of recent research and publications. The analysis of modern theater shows that electricity consumption in optical technologies in the agrarian sector of the economy is 15-20% of the total expenditures in the industry. This attaches particular importance to the problem of energy conservation in irradiation technologies, an important place among which is the cultivation of plants in closed soil [1,2]. Application of mathematical modeling for irradiation of plants in closed soil is considered as one of the directions of energy conservation.            It should be borne in mind that there are no common recipes for constructing models. The model should reflect only the most important features of the research object, remaining to avoid simple, without secondary factors [4].The purpose of the research is to develop a polycrystalline mathematical model of the process of growing vegetables in the greenhouse and to solve with it the question of optimizing the process of plant irradiation, taking into account the features of the technological process, the type of plant, and so on.Materials and methods of research. The main factors influencing the development and growth of plants are: optical radiation, assimilation of nutrients, the influence of temperature and moisture. The model of the dependence of the growth of plant productivity on the characteristics of the regime of radiation and other key factors in general terms can be represented as a expression. The law of distribution of change in the temperature of air in the greenhouse is simplified taking close to the sinusoidal. When modeling the process of absorption of moisture should take into account the fact that most of the moisture absorbed by plants immediately leaves it, evaporating into the atmosphere. Only about 1% of water goes to the growth of tissues and even less to photosynthesis.Under transpiration should be understood the process of passing moisture in the plant from absorption and to evaporation into the atmosphere.            The goal of optimization in protected ground structures is to achieve an extreme result:            • If the output of the process is the increase in yield, then it (the result) should seek maximum value;            • If the output result is a reduction in the cost price of the manufactured product, then this result should be sought to a minimum.            Thus, it is clear that solving the problem of optimization in relation to the reduction of the cost of production it is necessary to find the optimal (effective) values of the factors of influence by the proposed polycrystalline method. :            Moreover, this can be done in the most appropriate ways: taking into account all factors at once, or determining each factor separately. Different methods can be used for definition and analysis of factors: mathematical, experimental, Delphi expert estimation method, etc.            Conclusions. Getting quality agricultural products at minimal cost for its production is impossible without creating quality conditions for its cultivation. To select the optimum conditions for growing crops, it is necessary to take into account information about their condition, consider the plant as an object of regulation and develop an appropriate system for regulating the parameters of the environment environment as a feedback system. The application of mathematical modeling of optical technologies in closed soil systems is considered as one of the main options for solving energy saving issues in plant cultivation and obtaining quality products.